Acute Pancreatitis – Etiology, Pathogenesis, Pathophysiology and The Current Trend in Its Management and Prevention - Derrick Derrick; Frandy Frandy; Antonius Dian Wirawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Acute pancreatitis is an episode of cellular injury and inflammation of the pancreas parenchyma triggered by autodigestion of pancreatic parenchyma by abnormally activated pancreatic enzymes, its manifestations ranges from mild, moderate-severe and severe pancreatitis. Most episode of acute pancreatitis resolved completely while some develop recurrent acute pancreatitis and in turn progressing to chronic pancreatitis and its sequelae. While many etiologies known may cause acute pancreatitis, current theories propose three mechanism that may be involved in the pathogenesis of acute pancreatitis i.e. duct obstruction, direct acinar injury and defective intracellular transport. Recommendations from current guidelines are very useful to treat acute pancreatitis, few groundbreaking changes from the previously dated guidelines on treating acute pancreatitis are also made,providing us dated evidence-based approach to treat acute pancreatitis. Judicious and aggressive treatment are needed to minimize the damaged area of involved pancreatic parenchyma. Holistic prevention is neededto minimize the incidence of acute pancreatitis, pushing down the numbers of recurrent acute pancreatitis and ultimately may decrease the incidence of chronic pancreatitis and its sequelae.